Preliminary analysis of a birth cohort study (Go-Child) assessing wheeze and atopy in infancy. (24th May 2012) - Inglis, S; Chakraborty, S; Basu, K; Quin, M; Allen, R; Abd, A; Macgregor, D; Seddon, P; Rabe, H; Palmer, C; Memon, A; Mukhopadhyay, S
Abstract : Aims: Wheeze during infancy may be related to development of asthma in childhood. Most studies that have explored this question have been retrospective and have not assessed wheeze at 1 year of age. We have established a genotyped birth cohort (GO-CHILD) to investigate the influence of genetic and environmental factors on childhood atopy. The aim of this preliminary analysis of the cohort data is to identify the environmental risk factors for wheeze at age 1 year. Methods: Participants were recruited antenatally. Following Ethics approval and informed consent, the expecting mothers completed a questionnaire on the antenatal risk factors of atopic diseases in the newborn. Family history of atopy was assessed. Details of environmental factors, like exposure to smoking during pregnancy, type of cooking fuel and socioeconomic background, were also collected. A postal questionnaire to assess atopic conditions, infections, feeding was administered at 1 year of age. The data from the antenatal and 1 year follow-up questionnaires were analysed by using SPSS version 16. The study aims to recruit 3000 UK mothers. This analysis only includes the Sussex data. Results: 66 (19%) of 341 participants developed wheeze by 1 year. 29% infants required hospital admission due to exacerbation of wheeze. The risk of wheeze was significantly increased in infants with maternal (p value <0.001 (OR 3.92; 95% CI, 2.10-7.32)) and paternal (p value 0.02 (OR 2.09; 95% CI, 1.09-4.01)) asthma. There was a significant increased risk of wheeze in infants attending nursery or playgroups (p value 0.02, (OR 1.93; 95% CI, 0.87-1.57)).The risk of development of wheeze in infants with eczema was significantly increased compared to those without eczema (p 0.05, (OR 1.90; (95% CI, 0.99-3.63)). Conclusions: This is the first large prospective study with detailed phenotyping of wheeze at the end of the first year of life. It shows that infants with eczema, family history of asthma and those attending nursery or playgroups are at increased risk of developing wheeze during the first year of life. An earlier presentation of wheeze is associated with more number of attacks of wheeze over the first year of life. Funded by SPARKS